Treatment with oxfendazole increased levels of cardiac troponin I in pigs naturally infected with Taenia solium cysticercosis - Chibeza Zulu; Isaac K. Phiri; Kabemba E. Mwape; Martin C. Simuunza; Muloongo C. Sitali; Racheal Mwenda; Veronika Schmidt; Mwelwa Chembensofu; Maxwell Masuku; Andrea S. Winkler; Chummy S. Sikasunge (PLoS ONE, 2025)
Background Experimental pigs have been used to study human Taenia solium cysticercosis and neurocysticercosis. Biomarkers such as cardiac troponin I (cTnI) have been used to study various disease states such acute myocardial infarction (AMI) and the effect these diseases have on this molecule. However, no studies have been done to establish the effect of anthelminthic treatment on cTnI in pigs with cysticercosis and the role this biomarker plays with regards to inflammation following treatment. Objective To investigate the effect of anthelminthic treatment on cardiac troponin I (cTnI) levels in pigs naturally infected with cysticercosis. Materials and methods A total of 36 pigs were included in this study and were assigned to either the positive (+ve) or negative (-ve) groups based on cysticercosis infection status as determined by tongue examination and Ag-ELISA (apDIA-Belgium). Pigs in each group were then randomly assigned to either treated or not-treated (control) groups. Treatment was done using oxfendazole (OXF) at effective dose of 30mg/kg orally. Baseline serum samples were collected prior to treatment and thereafter at 24hrs, 48hrs and 72hrs post treatment. This was followed by weekly sampling up to 11 weeks post treatment. Laboratory and statistical analysis of cTnI was done using Ag-ELISA and GraphPad prism software (9.0.0 version) i.e., two-way repeated measures ANOVA, respectively. Carcass dissections were done 12 weeks post treatment, and a correlation analysis was performed to establish the relationship between cTnI concentration and number of cysts in the positive pool of pigs. Results Both hourly and weekly observations post-treatment revealed a significantly high concentration of cTnI in the infected and treated (IT) group (mean = 0.041 ± 0.002 ng/ml) in comparison to the other treatment and control groups, i.e., infected and not-treated (INT) group (mean = 0.024 ± 0.009 ng/ml) (p = 0.015) as well as the negative groups [not infected and treated (NIT) (mean = 0.016 ± 0.0009 ng/ml) (p = 0.003) and not infected and not treated (NINT) (mean = 0.014 ± 0.006 ng/ml)(p = 0.001)], respectively, throughout the observation period. This study shows that there was a strong relationship between cardiac damage/inflammation and the rise in cTnI concentration following treatment with OXF. Pearson correlation analysis results revealed a strong positive correlation between the number of active cysts and the concentration of cTnI in the INT group. Conclusions This study shows that OXF treatment of pigs with T. solium cysticercosis results in increased concentration of cTnI possibly due to the cardiac damage/inflammatory response following treatment as the cysts degenerate/calcify. This makes cTnI a very good biomarker for cardiac injury/damage following treatment in pigs with cysticercosis.